A nanostructured covalent organic framework with readily accessible triphenylstibine moieties for high-performance supercapacitors. Issue 22 (25th February 2022) - Kang, Kun; Wu, Zhengyi; Zhao, Miaomiao; Li, Zijie; Ma, Yunlong; Zhang, Jingmin; Wang, Yan; Sajjad, Muhammad; Tao, Rao; Qiu, Li
Abstract : The well-uniform nanostructures of Sb-COF make triphenylstibine moieties readily accessible by the electrolyte, and the assembled Sb-COF//rGO thus provides an excellent energy density of 69 W h Kg −1 . Abstract : A pristine, redox-active triphenylstibine based COF (Sb-COF) exhibits well-uniform nanostructures which could provide sufficient electron conduction pathways and minimize the ion transport lengths, making triphenylstibine moieties readily accessible by the electrolyte. The assembled Sb-COF//rGO thus provides an excellent energy density of 69 W h Kg −1 .